2005
DOI: 10.1111/j.1540-8191.2005.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Artery Grafting in Patients with Left Main Coronary Artery Disease

Abstract: Patients with LMCD can undergo OPCAB grafting safely and effectively despite reduced LVEF. LMCD should no longer be seen as a contraindication to perform OPCAB grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
2
20
1
2
Order By: Relevance
“…Murzi et al (13) again showed this difference in practice; the OFP received fewer grafts and had a lower rate of complete revascularization. The same was evident in Virani et al (11) paper; the average number of grafts was 3.1 in OFP and 4.1 in ONP surgery (P=0.004).…”
Section: Concernssupporting
confidence: 65%
See 3 more Smart Citations
“…Murzi et al (13) again showed this difference in practice; the OFP received fewer grafts and had a lower rate of complete revascularization. The same was evident in Virani et al (11) paper; the average number of grafts was 3.1 in OFP and 4.1 in ONP surgery (P=0.004).…”
Section: Concernssupporting
confidence: 65%
“…Virani et al (11) found no difference in major complications i.e., stroke, myocardial infarction, renal failure, sternal wound infection between OFP and ONP. However, mean hospital length of stay favored the OFP.…”
Section: Morbiditymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Merharwal et al have found a similar outcome of OPCAB and on-pump surgery in patients with multi-vessel disease and overall higher risk [15]. Finally, Virani et al reported on the safety of OPCAB inpatients with LMD and reduced ejection fraction (EF) [16]. OPCAB practice is now widely accepted and expands further.…”
Section: Introductionmentioning
confidence: 94%